Interaction of Botulinum Toxin with the Epithelial Barrier. (26th January 2010) - Fujinaga, Yukako
Abstract : Botulinum neurotoxin (BoNT) is a protein toxin (~150 kDa), which possesses a metalloprotease activity. Food-borne botulism is manifested when BoNT is absorbed from the digestive tract to the blood stream and enters the peripheral nerves, where the toxin cleaves core proteins of the neuroexocytosis apparatus and elicits the inhibition of neurotransmitter release. The initial obstacle to orally ingested BoNT entering the body is the epithelial barrier of the digestive tract. Recent cell biology and molecular biology studies are beginning to elucidate the mechanism by which this large protein toxin crosses the epithelial barrier. In this review, we provide an overview of the structural features of botulinum toxins (BoNT and BoNT complex) and the interaction of these toxins with the epithelial barrier.